Insight into Trypsin Miscleavage: Comparison of Kinetic Constants of Problematic Peptide Sequences - Šlechtová, Tereza; Gilar, Martin; Kalíková, Květa; Tesařová, Eva (Analytical chemistry, 2015)
Trypsin, a high fidelity protease, is the most widely used enzyme for protein digestion in proteomic research. Optimal digestion conditions are well-known and so are the expected cleavage products. However, missed cleavage sites are frequently observed when acidic amino acids, aspartic and glutamic acids, are present near the cleavage site. Also, the sequence motifs with successive lysine and/or arginine residues represent a source of missed cleaved sites. In spite of an adverse role of missed cleaved peptides on proteomic research, the digestion kinetics of these problematic sequences is not well-known. In this work, synthetic peptides with various sequence motifs were used as trypsin substrates. Cleavage products were analyzed with reversed-phase high performance liquid chromatography, and the kinetic constants for selected missed cleavage sites were calculated. Relative digestion speed for lysine and arginine sites is compared, including the digestion motifs flanked with aspartic and glutamic acid. Our findings show that DK and DTR motifs are cleaved by trypsin with 3 orders of magnitude lower speed than the arginine site. These motifs are likely to produce missed cleavage peptides in protein tryptic digests even at prolonged digestion times.
Keywords: trypsin; kinetika; Substrate Specificity; Glutamic Acid; kyselina glutamová; Trypsin; sekvence aminokyselin; Amino Acid Motifs; Sequence Analysis, Protein; kyselina asparagová; Aspartic Acid; aminokyselinové motivy; sekvenční analýza proteinů; Amino Acid Sequence; substrátová specifita; Kinetics